2021
DOI: 10.1021/acs.est.1c04031
|View full text |Cite
|
Sign up to set email alerts
|

Organofluorine Mass Balance Analysis of Whole Blood Samples in Relation to Gender and Age

Abstract: Studies have highlighted the increasing fraction of unidentified organofluorine (UOF) compounds in human blood, whose health effects are not known. In this study, 130 whole blood samples from the Swedish general population were analyzed for extractable organofluorine (EOF) and selected per-and polyfluoroalkyl substances (PFAS). Organofluorine mass balance analysis revealed that 60% (0−99%) of the EOF in female samples could not be explained by the 63 monitored PFAS; in males, 41% (0−93%) of the EOF was of unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 63 publications
(131 reference statements)
3
28
1
Order By: Relevance
“…Progress in this area will greatly improve understanding of the importance of human exposure to pre-PFAAs and will contribute to closing the mass balance on organofluorine in human blood. Total organic fluorine measurements indicate the likely presence of unknown PFASs in human blood from the general population, , but only a handful of novel PFASs have been identified in human serum. , The presence of unidentified pre-PFAAs, including intermediate transformation products, has been raised as a potential contributor to the unknown PFAS fraction in serum from the general population …”
Section: Pre-pfaas In the Human Bodymentioning
confidence: 99%
“…Progress in this area will greatly improve understanding of the importance of human exposure to pre-PFAAs and will contribute to closing the mass balance on organofluorine in human blood. Total organic fluorine measurements indicate the likely presence of unknown PFASs in human blood from the general population, , but only a handful of novel PFASs have been identified in human serum. , The presence of unidentified pre-PFAAs, including intermediate transformation products, has been raised as a potential contributor to the unknown PFAS fraction in serum from the general population …”
Section: Pre-pfaas In the Human Bodymentioning
confidence: 99%
“…7,8 Target and extractable organic fluorine screening indicate that legacy PFASs contribute to a small proportion of total fluorine in humans, and a large number of novel PFASs are unknown. 9 At present, only a few toxicology studies have found that some perfluorinated alternatives may persist longer in humans, causing greater toxicity and potential health risks. 10,11 Therefore, novel PFASs may pose a potential hazard to human health.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrosubstituted PFCAs (H-PFCAs). Six peaks (m/z 344.98−594.96) were identified as H-PFCAs (C = 7,8,9,10,11,12). The molecular formula error was between −2.83 and 0.65 ppm, and the RT increased with the number of carbon atoms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent studies have identied EOF and different classes of emerging PFAS in various environmental media. [23][24][25][26][27][28][29] These techniques, however, were mostly applied to wastewater or biota samples. Studies focusing on drinking water are limited.…”
Section: Introductionmentioning
confidence: 99%